Chlordiazepoxide (Librium) and Tests of Thyroid Function. Issue 5704 (2nd May 1970) - Clark, Frederick; Hall, Reginald
Abstract : The effect of chlordiazepoxide (Librium) on thyroid function was examined in 14 euthyroid patients who required the drug for psychiatric reasons and in six patients with clinically mild thyrotoxicosis. There was no significant difference in results from tests of thyroid iodide trapping (thyroid radioiodine uptake, thyroid clearance, and absolute iodine uptake) or of thyroid hormone release (protein-bound iodine, T3 resin uptake, and free thyroxine index) carried out before and during treatment with the drug over a four-week period. It is suggested that chlordiazepoxide need not be withdrawn before thyroid status and function are assessed in any patient taking the drug.